An acoustic valve within the nose of sperm whales Physeter macrocephalus - Huggenberger, Stefan; Andre, Michel; Oelschlaeger, Helmut H. A. (WILEY-BLACKWELL, 2014)
Sperm whales Physeter macrocephalus emit impulsive sound signals in short series of rhythmic clicks (codas) for communication, and in long series of single acoustic events (usual clicks) for echolocation. Both click types are generated pneumatically within the hypertrophied nasal complex, at the monkey lips' at the rostral end of the right nasal passage. Each individual click comprises repetitive pulses decaying in intensity. However, the decay rate is distinctly higher in usual clicks than in coda clicks. The mechanism of decay rate control in the clicks is still unclear, and it is unclear why the right nasal passage crosses the nasal acoustic pathway between two hypertrophied acoustic fat bodies (spermaceti organ, junk), so that it resembles a bent acoustic horn'. We present a new concept to explain how the flat right nasal passage can serve as a variable acoustic valve, and how the amount and distribution of its air filling can be controlled by muscle action. This mechanism allows the whale to determine the pulse decay rate and thus switch between the two modes of click production. Coda clicks are generated by reverberations within the spermaceti organ (partial trapping of sound) and by the release of sound energy in fractions through the air-filled right nasal passage. In contrast, echolocation clicks as single events are released during the partial collapse of the right nasal passage between the spermaceti organ and the junk. This interpretation of the right nasal passage as an adaptive acoustic valve elucidates why the spermaceti organ and the junk are separated from each other by an air-filled space of variable volume crossing the sound path of the bent acoustic horn' in the posterior part of the nasal complex.